PENGARUH RETURN ON EQUITY, LEVERAGE DAN SALES GROWTH TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA TAHUN 2013 - Tyas Prastika; Dahlia Br. Pinem (Ekonomi dan Bisnis, 2015)
This study is performed to examine the influence of variable Return On Equity, Debt to Equity Ratio and Sales Growth on Dividend Policy in go public companies in the Indonesian stock exchange (IDX) at 2013. The population in this study is listed companies in Indonesian Stock Exchange at 2013. Obtained a total sample of 44 companies. The analysis technique used here is multiple linear regression and hypothesis test using F and t statistic with level of significance 5%. The results showed that the Return On Equity, Debt to Equity Ratio and Sales Growth simultaneously influence on Dividend Policy. The coefficient of determination (R2) in this research was 0.149 that means 14.9% dividend policy can be explained by the variable Return On Equity, Debt to Equity Ratio and Sales Growth, while the remaining 85.1% explained by other variables that are not used in this study. Partially, only Sales Growth variable has negative influence on Dividend Policy.